Design and Development of a Website-Based “Agriplan” Information System to Help Plant Care - Wila Marviani BJ; Santi Ika Murpratiwi; Dwi Ratnasari; Herliana Rosika (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2024)
Agriculture has been an important part of human life for a long time, with farmers as the main drivers. Farmers often face the challenge of increasing land conversion, especially in West Nusa Tenggara (NTB) with population growth and the need for land for housing, offices, and government facilities. As a result, every year around 10,000 hectares of agricultural land in NTB shrinks from a total of 270,000 hectares, causing an increase in raw material prices, economic decline and loss of farmer jobs. This research aims to develop a Website-Based “Agriplan” Information System to Assist Plant Care, to support the management of narrow agricultural land with access to agricultural information and solutions. Development using Personal Extreme Programming method, with a qualitative approach through observation and interviews, as well as Black Box Testing and User Acceptance Testing. The test results show that 90.04% of this system is effective in supporting sustainable agriculture.